Plant viruses highlighted - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Sources of resistance to viruses of pepper (Capsicum spp): a catalog by S K Green and J S Kim 1994 AVDRC Publication 94-421 ISBN 90 9058 087 9